P227Microparticles in systemic circulation of patients with acute coronary syndrome. (15th July 2014) - Malinova, L; Mironova, A; Portnov, S; Tarakanchikova, YA; Zakharevich, A; Denisova, T; Tuchin, V
Abstract: The purpose of the study was to compare quantitative parameters of microparticles (MP) in systemic circulation of patients with acute coronary syndrome (ACS) and to estimate their clinical implication. Materials and methods: 30 patients with acute coronary syndrome (ACS) 45 … 84 yo were included in the study: unstable angina (UA, n = 12) and myocardial infarction (MI, n = 18). High magnification images of MP were obtained using Mira II LMU scanning electron microscope. Size distribution and zeta potential were measured by means of the Zetasizer Nano ZS Analyser. Results. No differences in blood lipids, creatinine, bilirubin and screening coagulation tests (UA vs MI) were detected. Glucose levels were slightly higher in patients with MI vs UA (5.36±0.2 vs 5.82±0.8mmol/L, p = 0.009). Total protein (64.0 (63.0;66.0) vs 69.0 (66.0;73.0) g/L, p = 0.000) and fibrinogen (2.4 (1.8;2.4) vs 3.0 (2.9;3.9) g/L, p = 0.000) were significantly lower in patients with UA. According to particles' size three pools of MP in systemic circulation of patients with ACS were detected: 1st – 35-70 nm, 2nd – 9-21 nm and 3d – 300 nm and larger. There were no differences in diameter and shape of MP of similar size, of first two "types" of MP in all studied patients (p = 0.777; 0.745). The largest MP more frequently (35% vs 75%) were detected in MI group and were the largest particles detected in systemic circulation in patients with ACS (4312.0 (295.7; 4690.0) nm vs 5068.5 (4607.7; 5174.0) nm, p = 0.017). The peaks intensity differed significantly in patients with UA vs MI: peak 1 – 78.8 (75.6; 84.5) vs 89.8 (82.7; 98.45)%, p = 0.000; peak 2 (17.4 (12.7; 20.6) vs 12.0 (4.2; 15.4)%, p = 0.007). Zeta potential was significantly lower in UA vs MI (-7.8 (-8.5; -6.9) vs -8.8 (-9.6; -8.3) mV, p = 0.009). Both diameter and intensity of peaks 1 had significant negative correlation with age (R = -609, p <0.05), monocyte count (R = -681, p < 0.05). Peak 3 diameter correlated with creatine phosphokinase and troponin concentrations (R = 0.509, p <0.05). Peak 2 intensity positively correlated with platelet count (R = 0.435, p < 0.05). Conclusions: Standard MP analyser is suitable for express estimation of MP secretion in systemic circulation. Tentative results suppose at least three sources of MP production in ACS, nevertheless further investigation of correlation within morphology and origin of MP is necessary. Intensity of MP secretion in systemic circulation was significantly higher in patients with MI, and correlated with important predictors of clinical course in patients with ACS.